Congenital dynamic cervical instability in a dog: the role of computed tomography and 3D printing to plan and optimize the surgical approach - Fernandes, Maria Eduarda dos Santos Lopes; da Silva, Ricardo Siqueira; de Lima, Leonardo Rodrigues; Ramos, Lucas Rego; Peixoto, Anna Julia Rodrigues; Brock, Gabriela Wacheleski; Coutinho, José Eduardo Silveira; Eleuterio, Eveliny de Oliveira; Adeodato, Alex Gradowski; Coelho , Cássia Maria Molinaro (Brazilian Journal of Veterinary Medicine, 2021)
This work aims to report the use of computed tomography (CT) and 3D printing technology in the diagnosis of dynamic instability with spinal compression, and the planning of cervical stabilization surgical of a 3-month-old canine with congenital cervical malformations. The patient had non-ambulatory tetraparesis, and a radiograph showed the fusion of the vertebral bodies from C3 to T3. A CT scan pinpointed the site of the spinal compression and revealed dynamic instability and severe spinal compression between the C2-C3 vertebrae. Tomographic images were processed to print a 3D prosthesis of the patient’s craniocervical-thoracic region to optimize and plan the necessary surgery. After studying the 3D prosthesis and selecting the surgical implants required, cervical stabilization surgery through ventral access was performed. The patient’s clinical improvement was rapid and progressive. Fifteen days post-surgery he was already in a quadrupedal position, after approximately 50 days he started walking again. In a year and a half of follow-up, the patient did not present any recurrence of the clinical signs. The conclusion was that CT and 3D printing contributed substancially for the clinical and surgical management, inferring quality, precision, and agility in the therapy undertaken.